Risk & Opportunities in Development of new Drugs: A New Perspective - Shubham Kumar; Sweta Ravindra Singh (Recent Trends in Infectious Diseases, 2023)
The procedures of drug discovery and development are briefly described in this article. Our goal is to assist researchers whose work may be pertinent to the discovery and/or development of new drugs in framing their research reports in a way that appropriately situates their findings within the drug discovery and development process and supports the efficient translation of preclinical research to humans. One overarching theme of our article is the length, complexity, and expense of the process, which forces the consideration of numerous biological targets for every new drug that is eventually approved for clinical use as well as the potential need for new research tools to examine each new target. The efficacy of the development process can be increased by studies that help to resolve any of the numerous scientific and practical problems that are involved in it. By being aware of these problems, actions can be taken early to improve chances of success. Drug Regulatory Affairs refers to all facets of the pharmaceutical process of drug discovery and research, which also addresses numerous risks and opportunities of drug development, and which are subject to varying degrees of regulations of various nations, including India, the United States, and Europe. The pharmaceutical law framework is employed as guidelines on Quality, Safety, and Efficacy of a Drug as well as Health Authorities' Attitudes and Requirements are Employed for the Correct Pathway of Pharmaceutical Needs and Have A Great Influence On The Drug Development Process And Had Success Through It. Professionals in regulatory affairs interact with each of these elements in order to achieve the intended outcome of drug development. The health authorities are designed to direct and analyses the medication that satisfies the required standards for quality and efficacy.
Keywords: Drug discovery; natural resources; opportunities; patient health; pharmacology